Influence of guidance knowledge and counseling services and attitudes toward guidance on the performance of guidance teachers in high schools - Samad, Sulaiman; Malik, Anas (Psychology in the schools, 2023)
Guidance and counseling teachers play an important role in students' career planning and dealing with students' problems. The primary objective of this study is to examine the influence of knowledge of guidance and counseling services as well as attitudes toward guidance on the performance of high school guidance teachers by measures of partial and multiple correlation. This study was conducted with a quantitative approach using the explanatory survey method. By employing a simple random sampling technique, the sample obtained consisted of 145 junior and senior high school guidance teachers. The data was analyzed with descriptive statistics using regression test methodology. The study results show that the level of knowledge of guidance and counseling for guidance teachers falls in the “moderate” category, the attitudes toward guidance tend to be on the positive side, whereas the results suggest the performance of guidance teachers is in the “high” category. It was found that the influence of knowledge of guidance and counseling services is positive and significant on the performance of guidance teachers. The influence of attitudes toward guidance is positive and significant on the performance of guidance teachers. Knowledge of guidance and counseling services and attitudes toward guidance jointly influence the performance of high school guidance teachers. Practitioner points The performance of guidance teachers is in the “high” category. The knowledge of guidance and counseling services is positive and significant on the performance of guidance teachers. The attitude toward guidance is positive and significant on the performance of guidance teachers.